Reduction in hospital admissions for acute coronary syndrome after the successful implementation of 100% smoke-free legislation in Argentina: a comparison with partial smoking restrictions. Issue 4 (20th May 2011) - Ferrante, D; Linetzky, B; Virgolini, M; Schoj, V; Apelberg, B
Abstract : Background: Several studies have shown a decrease in acute coronary syndrome (ACS) admissions after the implementation of 100% smoke-free legislation. However, no studies have been conducted in developing countries. Methods: We conducted a time series analysis of ACS hospital admissions in Santa Fe province and Buenos Aires city, Argentina. In 2006, Santa Fe implemented a 100% smoke-free law and Buenos Aires implemented a partial law with designated smoking areas and exceptions. Age-standardised ACS admissions rates were compared before and after the implementation of the laws in each district. Smoking prevalence, compliance with legislation and exposure to secondhand smoke (SHS) was also assessed in both districts. Results: In Santa Fe an immediate decrease in ACS admissions was observed after implementation (−2.5 admissions per 100 000, p=0.03; 13% reduction), compared with no change in Buenos Aires city (rate ratio Santa Fe vs Buenos Aires: 0.74, 95% CI 0.63 to 0.86, p≤0.001). In Santa Fe, the immediate effect was followed by a persistent decrease in admissions due to ACS (−0.26 admissions per 100 000 per month). Smoking prevalence did not change significantly in either district during the same period. In both districts, there was a reduction in self-reported SHS exposure, with a trend towards lower exposure in Santa Fe province. No other comprehensive tobacco control interventions were implemented during the study period. Conclusions: A 100% smoke-free law was more effective than a partial restriction law in reducing ACS admissions. An immediate effect was followed by a sustained decrease in ACS admissions. Smoke-free initiatives can be also effective in decreasing acute coronary events in developing countries.